Uridine alleviates carbon tetrachloride‐induced liver fibrosis by regulating the activity of liver‐related cells. Issue 3 (30th December 2021) - Zheng, Wei V.; Li, Yaqin; Cheng, Xianyi; Xu, Yanwei; Zhou, Tao; Li, Dezhi; Xiong, Yu; Wang, Shaobin; Chen, Zaizhong
Abstract: At present, liver fibrosis is a major challenge of global health. When hepatocyte regeneration cannot compensate for hepatocyte death, it will develop into liver fibrosis in chronic liver disease. Initially, collagen produced by myofibroblasts plays a role in maintaining liver integrity, but excessive collagen accumulation can inhibit the residual liver function, leading to liver failure. At present, many scientists are actively looking for drugs to alleviate liver fibrosis. In the current study, we investigated the potential role of uridine in the treatment of liver fibrosis (uridine is a plant/animal‐derived pyrimidine nucleoside, therefore uridine can also be ingested and absorbed by the body, accompanied by the process of food intake). For this, we systematically studied the effect of uridine on CCl4‐induced liver fibrosis in vitro and in vivo through a series of technologies, such as Western blot, laser confocal scanning microscope, ELISA and immunohistochemistry. The experimental results showed that uridine can effectively reduce the accumulation of collagen in liver. Furthermore, uridine can improve the activity of liver cells and alleviate CCl4‐induced liver injury. Furthermore, uridine can significantly alleviate the risk factors caused by hepatic stellate cell activation, uridine treatment significantly down‐regulated the expression of α‐SMA, collagen type‐I and fibronectin. In conclusion, the current research shows that uridine can alleviate CCl4‐induced liver fibrosis, suggesting that uridine can be used as a potential drug to alleviate liver fibrosis.